Knowledge, Attitude, and Practices Toward SARS-COV-2 Infection in the United Arab Emirates Population: An Online Community-Based Cross-Sectional Survey - Alremeithi, Hamda Musabbah; Alghefli, Aljazia Khalfan; Almadhani, Rouqyah; Baynouna AlKetbi, Latifa Mohammad (Frontiers in Public Health, 2021)
In the current situation involving the novel coronavirus disease (COVID-19), the disease containment depends mainly on the populations preventive practices and self-isolation. In this study, we explored the adult populations approach towards COVID-19 in UAE between the 4th and 14th of April 2020. We used a community-based, cross-sectional study using a self-administered electronic questionnaire covering five different aspects: demographics, knowledge, practice, attitude, source and trust of information, and a patient health questionnaire (PHQ-2) for depression screening. A total of 1,867 people responded to the survey. Knowledge results were better in people with higher education levels, non-UAE nationals, those with a higher PHQ-2 score, or with a positive contact history with a SARS-COV-2 infected patient. The best practice scores were shown by participants with high knowledge scores and education levels. Depression risk was significantly higher in men, non-UAE nationals, in those with lower knowledge scores, and younger ages. The most followed practices were staying home, handwashing, avoiding social gatherings, limiting three people per vehicle, and avoiding public transportation. The least practiced measures were covering the face while sneezing or coughing and wearing masks. Although staying home was reported by 92.5% of participants, 22.6% mentioned that they were visited by more than 2 people and visited others in 18.4% during the last week. Social media was the source of information for 82.1% of the participants, and most trusted doctors and healthcare providers. A depression risk was present in 18.9% of the participants and the majority of respondents agreed that SARS-COV-2 infection will finally be successfully controlled. The obtained results on knowledge and practices, although satisfactory, could be insufficient to prevent this pandemic from being contained. We recommend the intensification of awareness programs and good practices. Mental health is an area worth further studies.